Long Noncoding RNA Small Nucleolar Host Gene: A Potential Therapeutic Target in Urological Cancers - Yang, Zitong; Li, Qinchen; Zheng, Xiangyi; Xie, Liping (Frontiers in Oncology, 2021)
The incidence of urological cancer has been gradually increasing in the last few decades. However, current diagnostic tools and treatment strategies continue to have limitations. Substantial evidence shows that long noncoding RNAs (lncRNAs) play essential roles in carcinogenesis and the progression, treatment response and prognosis of multiple human cancers, including urological cancers, gastrointestinal tumours, reproductive cancers and respiratory neoplasms. LncRNA small nucleolar RNA host genes (SNHGs), a subgroup of lncRNAs, have been found to be dysregulated in tumour cell biology. In this review, we summarize the impacts of lncRNA SNHGs in urological malignancies and the underlying mechanisms.